Annotazioni sulla nozione di ἐξαίφνης nel Parmenide di Platone - Aiello, Miriam (B@belonline, 2020)
The paper inquires into the problems raised by the section on the instant – τὸ ἐξαίφνης – (155e-157b) in Plato’s Parmenides. Firstly, I will analyse the role and the meaning of the adverb ἐξαίφνης through a comparison of its occurrences in Plato’s works. Then, in the light of the different interpretative options set forth by the scholars, I will discuss the status of Parm. 155e-157b and the possible reasons why Plato provides this auxiliary inquiry on the instant after the conclusions of the second series of deductions. And finally, I will discuss more closely the deduction, the role, and the theoretical significance of τὸ ἐξαίφνης in Parm. 156d-e.